Bruxism and familiar functioning in school-age children between 5 and 11 years - Ana Lury Morales; Clotilde de la Caridad Mora Pérez; Ivelise Álvarez Rosa; Moraima Orbea González; Jeny Fernández Martínez; Jorge A. Rodriguez López (Medisur)
Background: Bruxism, a common negative habit in children, is often linked with emotional conflicts, anxiety, stress, or frustration, which could be originated in the familiar environment. Objective: To characterize the familiar environment of children between 5 and 11 years suffering from bruxism. Methods: Analytical control-case design, developed from March to June, 2007, including children between 5 and 11 years from three urban elementary schools included in Health Area II of Cienfuegos municipality. All the children with bruxism were selected as cases and the controls were selected through pairing 2 to 1. The test FF-SIL was used to assess familiar functioning. Results: Bruxism was not associated with gender. There were significant differences between both groups regarding familiar functioning, in which affectivity and cohesion had higher results and harmony was less significant. Most of the studied families were functional or half-functional. Most of children with bruxism come from families with inadequate functioning; besides, dysfunctional and severely dysfunctional families and more frequent in the group of children with bruxism. Conclusion: In the studied sample, bruxism was associated, to a large extent, with inadequate familiar functioning.